2015
DOI: 10.1002/jcp.24973
|View full text |Cite
|
Sign up to set email alerts
|

A New Medical Device Rigeneracons Allows to Obtain Viable Micro‐Grafts From Mechanical Disaggregation of Human Tissues

Abstract: Autologous graft is considered the gold standard of graft materials; however, this approach is still limited due to both small amount of tissue that can be collected and to reduced cell viability of cells that can be obtained. The aim of this preliminary study was to demonstrate the efficacy of an innovative medical device called Rigeneracons® (CE certified Class I) to provide autologous micro-grafts immediately available to be used in the clinical practice. Moreover, Rigeneracons® is an instrument able to cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
109
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 89 publications
(116 citation statements)
references
References 10 publications
6
109
0
1
Order By: Relevance
“…This evidence is in agreement with other recent papers in which the efficacy of this protocol in vitro was tested also in other type of tissues, including periosteum, biopsy of cardiac atria and lateral rectus muscle of eyeball 5 . In particular, we observed in Ded and dermis samples an increased cell viability after 7 days of culture, probably due to the use of a medium supplemented with 10% fetal bovine serum.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This evidence is in agreement with other recent papers in which the efficacy of this protocol in vitro was tested also in other type of tissues, including periosteum, biopsy of cardiac atria and lateral rectus muscle of eyeball 5 . In particular, we observed in Ded and dermis samples an increased cell viability after 7 days of culture, probably due to the use of a medium supplemented with 10% fetal bovine serum.…”
Section: Discussionsupporting
confidence: 93%
“…This protocol allows us not only to obtain viable but also autologous micro-grafts, given that the donor subject is also the acceptor of these micro-grafts. The capacity of this system to obtain autologous micro-grafts was especially reported in the field of dentistry where it has been shown that transplantation of autologous Dental Pulp Stem Cells (DPSCs) in a non-contained infrabony defect contributed to periodontal repair and regeneration of atrophic maxilla 5,6 . The ability of these micro-grafts to improve the wound healing process was also previously reported in the management of complex wounds after surgical interventions or complications 4 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some techniques allow for the correction of bone defects by grafting adult mesenchymal cells [160]. The use of nanofeatured surfaces, in association with these bone regeneration techniques, could allow for better new-bone formation and ultimately improve osseointegration and implant success.…”
Section: Differentiationmentioning
confidence: 99%
“…Nevertheless, some investigators have devised a new clinical process of tissue regeneration, using an enzymatic 92 and a mechanical disaggregation. 93 The novel strategy permits a mechanical disaggregation of the tissue without manipulating the matrix. The mechanical isolating procedure is easier to use, safer, less expensive and more rapid proving it more advantageous compared to the current enzymatic procedures in use.…”
Section: Treatments For Ibd: Future Perspectivesmentioning
confidence: 99%